USER INTERFACE / USER EXPERIENCE ANALYSIS AND DESIGN ON E-RESOURCES CENTER WEBSITE DINAMIKA UNIVERSITY USING USER CENTERED DESIGN (UCD) METHOD - Dita Permata Sari; Endra Rahmawati; Nunuk Wahyuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Universitas Dinamika (Undika) is one of the universities in The City of Surabaya located Jalan Raya Kedung Baruk No. 98 which has a variety of facilities and services provided for all academic community. One of them is Undika Library which of course also has a variety of facilities and services provided and one of those services is an e-resources center. E-resources center prioritizes in providing additional information for academic community as a support for academic activities. However, the problem through observation and interview concluded that 36.7% knew while 63.3% were not aware of the e-resources center service. Based on the problem, researchers have conducted analysis and design of user interface / user experience and produced a prototype e-resources center website using user centered design method consisting of Plan the User Centered Design process, Understand and specify context of use, Specify user requirements, Product design solutions, Evaluate design agains requirements. In the process of testing or evaluating the prototype to 51 respondents, it was carried out using the webuse method which served as a benchmark for views and responses to users. So it is obtained from the test results that the results of the prototype design obtain an average value on all indicators of 89.5% where the design can be well received by users.  Keywords: User Interface, User Experience, User Centered Design, Webuse